Teacher's Self-Efficacy of Prospective Mathematics Teacher Students in Micro Teaching - Mentari, Violin Putri; Pratama, Fika Widya (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
A teacher's self-efficacy is a teacher's belief regarding the ability to plan and implement learning successfully in a situation. As prospective teachers, students must have skills in teaching, therefore students usually do micro-teaching before implementing learning in the school environment. Microteaching is carried out to train and improve teaching skills on a micro-scale. Besides that, teaching is also carried out in an effort to develop and improve the teaching profession. The purpose of this research is to identify Teachers' self-efficacy of mathematics education study program students in conducting micro-teaching as an excellent study program that produces quality graduates. The data collection techniques used in this study were surveys, interviews, and observations. This research used descriptive qualitative research, which was conducted on mathematics education students in the class of 2020 at Satya Wacana Christian University. Data analysis was conducted by combining the results of questionnaires and interviews with the results of the analysis of observations of teaching mathematics conducted by the subject based on the dimensions of teacher's self-efficacy. The dimensions measured were the teacher's self-efficacy toward student engagement, the teacher's self-efficacy toward classroom mastery, and the teacher's self-efficacy toward instructional strategies. This study used several additional instruments, namely questionnaires, observation sheets, interview guidelines, and documentation. The implementation of this research was carried out from April to January of the 2023/2024 academic year, with the result that students, as prospective teachers, fulfilled the three dimensions of teacher self-efficacy.